Nghiên cứu đặc tính sinh học của Saccharomyces Cerevisiae N9 và P6, ứng dụng vào lên men rượu vang - Đinh, Thị Kim Nhung (Bộ Giáo dục và Đào tạo, 2014)
The selection and indentification the names of 2 trains Saccharomyces cerevlsiae N9 and P6. The sesult shows that optimal is 24%; pure- line breeding medium 12- 14%; pH: 4,0 . Experiments on fermentation of there two trains Saccharomyces cerevisiae N9 and P6 have show good results. We put them in production of wine of 3000 Iitrets/ one time of production and the production have a good quality